Examining the Relationship Between Marketing Efforts and Visitor Satisfaction - Annita Jannah (JURNAL COMPUTECH & BISNIS, 2025)
This research addresses the critical issue of understanding the determinants of marketing's impact on visitor satisfaction. The study aims to explore how various relationship marketing dimensions influence guest satisfaction in the context of hostels in Bandung. To achieve this goal, the authors employed a survey approach, collecting data from 100 hostel visitors who had made at least two visits. The researchers utilized predictive testing through Partial Least Squares Structural Equation Modeling (PLS-SEM), a methodology commonly applied in marketing and management studies. The findings reveal that relationship marketing, encompassing financial bonds, social bonds, and structural bonds, has a positive and significant effect on visitor satisfaction. This study offers novelty by linking distinct dimensions of relationship marketing directly to visitor satisfaction in an under-researched area. The implications of these results suggest that hostel managers should focus on enhancing relationship marketing strategies to improve visitor experiences and ensure customer loyalty.